Biology of Neoseiulus californicus feeding on two-spotted spider mite - Maicon Toldi; Noeli Juarez Ferla; Catiane Dameda; Fernanda Majolo (Biotemas)
Tetranychus urticae (Koch) stands out as a polyphagous mite. In a strawberry plant, this mite develops on the underside of leaves, causing a significant injury. This study aimed to know the biological characteristics of Neoseiulus californicus (McGregor), from cultivated strawberry plants. The study started with thirty eggs isolated in arenas with different stages of T. urticae. The average length of egg-adult was higher for females (5.69±0.08) than for males (5.35±0.11). The sex ratio was 0.66 and the innate capacity for increase (rm) was 0.15 female/female/day. The net reproductive rate (Ro) was 17.10 times/generation, with an average to each generation (T) of 19.35 days. Greater oviposition was observed at the 11th day after its onset, with 2.7 eggs/female/day and the average was 38.14±5.58 eggs/female. The finite increase rate (?) was 1.41 female/day. Neoseiulus californicus showed to reproduce properly when feeding on T. urticae.